Customs Preferences of Territories with a Special Economic Status in the Asia-Pacific Region - Olga SINENKO; Igor MAYBUROV; Anna SASHCHENKO (Communications of International Proceedings, 2020)
The article presents a study of preferential customs treatment within special economic zones in the Asia-Pacific. The study aims to analyze customs incentives by type of special economic zones in the Asia-Pacific. The subject of the study is special economic zones in the Asia-Pacific region. The article presents a systematization of customs incentives within special economic zones in the Asia-Pacific. The authors analyze the formats and conditions of the provision of customs incentives in each type of special economic zones in the Asia-Pacific. The results are presented of a study into the practice of the application of preferential customs treatment within special economic zones in Russia. The authors show that flexible and rapidly developing special economic zones are the perfect potential growth areas thanks to tax and customs concessions and streamlined customs clearance procedures.
Keywords: Special Economic Zones; Asia-Pacific; Preferential Customs Treatment.